Pesticide Applications in Agricultural Systems - Manetto, Giuseppe; Cerruto, Emanuele; Longo, Domenico; Papa, Rita (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The effective and efficient application of PPP in agriculture is a very complex task, involving a lot of aspects ranging from active substance properties to climatic conditions, from target structure to equipment features, from operator awareness to the reference legislative framework. Some of these aspects have been treated in the six papers collected in this Special Issue on "Pesticide Applications in Agricultural Systems".